2016
DOI: 10.1088/0967-3334/37/9/1392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fetal QT interval using non-invasive fetal ECG technology

Abstract: Non-invasive fetal electrocardiography (NI-FECG) is a promising alternative continuous fetal monitoring method that has the potential to allow morphological analysis of the FECG. However, there are a number of challenges associated with the evaluation of morphological parameters from the NI-FECG, including low signal to noise ratio of the NI-FECG and methodological challenges for getting reference annotations and evaluating the accuracy of segmentation algorithms. This work aims to validate the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
(30 reference statements)
0
38
0
Order By: Relevance
“…We addressed these limitations in our study. Finally studies from Chia et al, Clifford et al, and Behar et al looked into the extraction of clinical parameters from the NI‐FECG morphology. Although these were original studies, all the fetuses included had no reported cardiac condition thus limiting the conclusions on whether the estimation of these physiological parameters is accurate enough and useful to provide actionable medical information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We addressed these limitations in our study. Finally studies from Chia et al, Clifford et al, and Behar et al looked into the extraction of clinical parameters from the NI‐FECG morphology. Although these were original studies, all the fetuses included had no reported cardiac condition thus limiting the conclusions on whether the estimation of these physiological parameters is accurate enough and useful to provide actionable medical information.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive fetal electrocardiography (NI‐FECG) is a promising noninvasive fetal diagnosis and monitoring alternative, which presents a number of advantages: low cost, possibility of local analysis (no need of long distance referral for pregnant women), information on atrial and ventricular activity, motion estimation, and possibility of continuous long‐term remote monitoring. The results of recent studies have shown the ability of the NI‐FECG to provide an accurate estimate of the fetal heart rate . However, to date, the clinical usability of NI‐FECG has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Analogously to the FMCG, the NI-FECG allows a deeper characterization of the electrophysiological activity by means of morphological analysis of its signal’s waveform. Promising early works on extracting morphological information from NI-FECG recordings have been published by Clifford et al (2011), Andreotti et al (2016a) and Behar et al (2016b).…”
Section: Fetal Ecg Recording Technique—state-of-the-art and Own Case-mentioning
confidence: 99%
“…A number of authors have used a rich variety of methods based on different principles for this purpose, as was mentioned in the previous section. For those cases in which only abdominal electrodes have been used to acquire the aECG signals, the fECG signals were extracted directly by means of linear [32,33,34,35,36,37,38,39,40,53,65,66,67,68,69,70,71,72] or nonlinear (for example, [73,74]) decomposition techniques [75,76]. …”
Section: State Of the Artmentioning
confidence: 99%